Statement by the Managing Director on the Work Program of the Executive Board : Executive Board Meeting, June 3, 2015. (Policy Papers; Policy Paper ;, 2015)
The Managing Director's Global Policy Agenda (GPA) presented to the IMFC in April identified a range of actions needed to bolster today's actual and tomorrow's potential output, diminish risks, and confront emerging global challenges. These actions included calibrating fiscal adjustment to economic conditions while establishing credible long-term fiscal frameworks and implementing growth-friendly fiscal policies, improving monetary policy effectiveness while containing excessive financial risk-taking, and accelerating structural reforms to raise growth potential and ensure inclusiveness. The GPA also outlined how the Fund would support the membership through assessments and policy advice provided in the context of multilateral and bilateral surveillance, financial support, and capacity building. This document translates the policy priorities laid out in the GPA and the IMFC communique into a work agenda for the Executive Board over the next 12 months. In particular, the Board will be engaged on several issues of multilateral scope, including quota reform and resources, the SDR basket review, challenges facing the international monetary system, and the post-2015 global development agenda. The work program also includes several items from the action plan of the 2014 Triennial Surveillance Review (TSR).